The impact of Toxoplasma gondii on the mammalian genome - Müller, Urs B (2020)
Nobody doubts that infections have imposed specialisations on the mammalian genome. However sufficient information is usually missing to attribute a specific genomic modification to pressure from a specific pathogen. Recent studies on mechanisms of mammalian resistance against the ubiquitous protozoan parasite, Toxoplasma gondii, have shown that the small rodents presumed to be largely responsible for transmission of the parasite to its definitive host, the domestic cat, possess distinctive recognition proteins, and interferon-inducible effector proteins (IRG proteins) that limit the potential virulence of the parasite. The phylogenetic association of the recognition proteins, TLR11 and TLR12, with T. gondii resistance is weak, but there is evidence for reciprocal polymorphism between parasite virulence proteins and host IRG proteins that strongly suggests current or recent coevolution.